Acute pancreatitis in children - Grzybowska-Chlebowczyk, Urszula; Jasielska, Martyna; Flak-Wancerz, Anna; Więcek, Sabina; Gruszczyńska, Katarzyna; Chlebowczyk, Wojciech; Woś, Halina (Gastroenterology Review/Przegląd Gastroenterologiczny, 2018)
Introduction : The acute pancreatitis is a rare disease, but it has started to be diagnosed more often in children. Aim : The aim of the study was single-centre, retrospective analysis of the incidence, aetiology, and clinical course of acute pancreatitis in children. Material and methods : We analysed the medical records of patients with acute pancreatitis hospitalised in the Gastroenterology Unit of the Paediatrics Department, Medical University of Silesia from Jan 2004 to Dec 2013. Results : There were 76 cases of acute pancreatitis among 51 children (average age: 12.07 years) hospitalised in the Gastroenterology Unit between January 2004 and December 2013. The diagnosis of acute pancreatitis was performed on the basis of INSPIRE criteria and modified Atlanta classification. Patients were divided into groups: I – 1–12 years old, which included 20 (39.21%) children and II – 13–18 years old, with 31 (60.78%) children. The idiopathic aetiology was the most common cause of acute pancreatitis, occurring in 22 (43.1%) children, and in 15 cases the aetiology of the disease was biliary (29.4%). Genetically determined causes were diagnosed in 8 (15.7%) patients, the PRSS1 mutation in four patients, mutation in SPINK1 in 1 child, and CFTR gene mutation in 1 child. Two children simultaneously had two genes mutations (CFTR, SPINK1), and during the considered period had more than one episode of acute pancreatitis. Conclusions : Acute pancreatitis of idiopathic aetiology was most common among the examined children, and this should encourage the continued search for the causes of disease, especially genetic, and with particular emphasis on younger age group.